Dampak Pandemi Covid-19 terhadap Persekutuan Jemaat di Gereja Kalimantan Evangelis Victoria Palangka Raya - Sri Angellyna (Sekolah Tinggi Teologi Baptis, Jakarta, 2021)
The impact of the COVID-19 pandemic has affected religious social life, as evidenced by changes in church worship patterns that affect Christian congregations' fellowship at GKE Victoria Palangka Raya. This study aims to describe the implementation of congregational fellowship and the impact of the pandemic on a congregational fellowship in terms of quantity and quality in each category. The research focused on GKE Victoria Palangka Raya using a qualitative approach. The results showed that the congregation's understanding of communion and changes in worship patterns impacted the quality of the congregation's faith. Moreover, congregations that rarely fellowship are less and less likely to worship. This has an impact on the decline in the quality of the congregation's faith, such as the emergence of groups, the technicality of following worship, not as it should be, and a shift in the concept of sacred worship. For this reason, the pandemic has positively and negatively impacted congregational fellowship, both in quality and quantity. AbstrakDampak pandemi COVID-19 mempengaruhi kehidupan sosial keagamaan, dibuktikan dengan perubahan pola ibadah di gereja yang mempengaruhi pesekutuan jemaat Kristen di GKE Victoria Palangka Raya. Tujuan penelitian ini yaitu mendeskripsikan implementasi persekutuan jemaat serta mendeskripsikan dampak pandemi terhadap persekutuan jemaat dari segi kuantitas dan kualitas di setiap kategorial. Penelitian difokuskan di GKE Victoria Palangka Raya menggunakan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa pemahaman jemaat tentang persekutuan serta perubahan pola ibadah berdampak kepada kualitas keimanan jemaat. Terlebih jemaat yang jarang bersekutu semakin jarang beribadah. Hal ini berdampak pada menurunnya kualitas iman jemaat, seperti: timbulnya kelompok-kelompok, teknis mengikuti ibadah tidak sesuai dengan yang seharusnya, serta pergeseran konsep kudusnya ibadah. Untuk itu, pandemi memberikan dampak positif dan negatif terhadap persekutuan jemaat baik secara kualitas maupun kuantitas.